Android-Based Inspection and Testing Analytical System of Electrical Safety - Nashruddin Anwar; Arief Marwanto; Muhammad Haddin (Universitas Islam Sultan Agung, 2022)
The process of inspection and testing of electrical safety nowadays is commonly done manually. This method has many weaknesses, one of them is the analysis result needs longer time and less accuracy. To overcome this problem, it needs an information system to inspect and to test the effectiveness of electrical safety. The purpose of this research is to design an android-based application which has function to become a tool to make electrical safety inspection and testing much easier. The parameter that will be used is administration documents checking, assessment, measurement, calculation, and testing. The android operation system is used to fasten the work process and get output that meet safety requirements. Black Box method is used to test the app and expected to fulfill the expectation and meet the goal. The result of this paper is that the app shows android-based inspection and testing system for electrical safety can be recommended for faster and accurate report